Response of riverine nitrogen export to human activities and meteorological factors in a typical agricultural watershed of eastern China - HAO Yun; LÜ Jun (浙江大学学报. 农业与生命科学版, 2022)
Non-point source nitrogen (N) pollution is one of the major environmental threats of water quality degradation in agricultural watersheds. Based on the monitoring data of N output at riverine outlet section and the calculation of net anthropogenic nitrogen input (NANI) in the Changle River watershed of Shengzhou City, Zhejiang Province from 2003 to 2016, the response relationships of riverine water quality to NANI and meteorological factors driving non-point source pollution were explored, and a response model was established to evaluate riverine N pollution sources in this study. The results showed that, during the study period, the average NANI was 95.77 kg/(hm2·a), among which chemical fertilizer N, net human food and animal feed N, atmospheric N deposition, biological N fixation and seed N contributed 53.90, 25.62, 11.94, 4.18 and 0.13 kg/(hm2·a), respectively. The average riverine N export was 2 178.78 t/a, which was positively correlated with NANI and precipitation, and negatively correlated with evaporation and wind speed in the studied watershed. Accordingly, the simulated results of the response model [R2=0.801 0, Nash-Sutcliffe efficiency coefficient (NSE)=0.799 1] showed that the historical remained N in the watershed, the NANI of the current year and the riverine background N accounted for 66.8%, 30.8% and 2.4% of the riverine N export, respectively. These results indicated that the historical remained N in the watershed was the largest contributor to riverine N pollution with a long-term impact on riverine water quality, which implied the existence of lag effect of riverine water quality in response to the measures of N emission reduction in the watershed. Therefore, the implementation of long-term N control measures should be an important strategy to prevent and control riverine N pollution in agricultural watershed.